A percepção das famílias sobre o brincar na pré-escola - Nascimento, Renata Dansiguer Santos do (2025)
This study addresses play in early childhood education and seeks to answer the following guiding question: What is the perception of families with children in the last year of preschool regarding play as a right and a formative element of learning? The initial hypothesis is that they understand the importance of play, but do not consider it a formative element for children's learning. Thus, the general objective is to analyze how families with children in early childhood education, especially in preschool age, five years of age, understand play as a right to learning and development. The participants are four mothers, two with children enrolled in a public institution and two with children enrolled in a private institution, both located in the city of Santo André. This is a qualitative research, with data produced through interviews with semi- structured questions. As for the theoretical framework, it is based on the concepts of childhood, children and play, supported by authors who have studied this topic, including Lev Vygotsky, Tizuko Morchida Kishimoto and Gisela Wajskop, from a dialectical materialist perspective. In addition, we were guided by current educational legislation, considering legal frameworks such as LDB, RCNEI and BNCC. Data analysis was inspired by Laurence Bardin's content analysis. That said, the results obtained indicate partial fulfillment of the research hypothesis initially outlined, given that the participants demonstrated an understanding of the relevance of play in the integral development of children, considering that they mentioned important aspects that are in fact related to play, such as socialization and motor improvement. In addition, they understand that there is an intentionality involved in the act of playing carried out under the mediation of the teacher at school. However, they demonstrated a still limited perspective on this practice when they point to the child as a passive subject, that is, one that needs to be molded so that they can develop meaningful experiences